Do migrant remittances spur financial development in Pakistan? evidence from linear and nonlinear ARDL approach - Faheem, Muhammad; Mohamed, Azali; Farooq, Fatima; Ali, Sajid (SPCRD Global Publishing, 2019)
The study asseses the influence of migrant remittances on financial development over the period of 1976-2018 in Pakistan. This study has applied the linear autoregressive distributive lag (ARDL) model and nonlinear autoregressie distributed lag (NARDL) model to check the symmetric and asymmetric effect of remittances. Results of the ARDL and NARDL bound test confirm remittances, FDI, real GDP and inflation significantly contributing to financial development. The outcomes of ARDL and NARDL have also confirmed the significant positive effect of migrant remittances on financial development in long-run. The asymmetric ARDL results show the existence of remittances nonlinear effect on financial development. Specifically, the study found remittances decrease have a significant impact while remittances increase have no any significant effect on financial development. Based on findings, this study recommends the plan for the policymakers of recipient countries, especially Pakistan, could harvest the potential gain of migrant remittances though positive asymmetric association with financial sector development.